Bisphenol A and food safety: Lessons from developed to developing countries. (June 2016) - Baluka, Sylvia Angubua; Rumbeiha, Wilson K.
Abstract: Modern lifestyles and changes in the socio-economic characteristics of households have stimulated current developments in food technology, processing and packaging. Chemicals such as bisphenol A (BPA) are known to migrate from food packaging into the food, resulting in human exposure to these chemicals. Similarly, BPA can migrate from baby feeding bottles into milk. BPA has been associated with adverse effects attributed to its estrogenic properties in various animal models. This review analyzed peer-reviewed publications in the English literature on human BPA exposure and regulations in developing countries compared to developed countries. BPA has been reduced or eliminated from food packaging and contact materials such as baby bottles in developed countries either voluntarily or by legislation. The meager data from developing countries shows that human BPA exposure in developing countries is similar to that in developed countries. With minor exceptions, BPA restriction, voluntary or legal, is virtually absent in developing countries of Africa, SE Asia, and South and Central America.